Spatial competition with capacity constraints and subcontracting - Matthias Hunold; Johannes Muthers (Johannes Kepler University of Linz, Department of Economics, 2018)
We characterize mixed-strategy equilibria when capacity constrained suppliers can charge location-based prices to different customers. We establish an equilibrium with prices that weakly increase in the costs to supply a customer. Despite prices above costs and excess capacities, each supplier exclusively serves its home market in equilibrium. Competition yields volatile market shares and an inefficient allocation of customers to firms. Even ex-post cross-supplies may restore efficiency only partly. We use our findings to discuss recent competition policy cases and provide hints for a more refined coordinated-effects analysis.
Keywords: L11; L41; L61; 330; Bertrand-Edgeworth; capacity constraints; inefficient competition; spatial price discrimination; subcontracting; transport costs